2022
DOI: 10.3390/cells11111797
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell-Based Regenerative Therapy and Derived Products in COPD: A Systematic Review and Meta-Analysis

Abstract: COPD is an incurable disorder, characterized by a progressive alveolar tissue destruction and defective mechanisms of repair and defense leading to emphysema. Currently, treatment for COPD is exclusively symptomatic; therefore, stem cell-based therapies represent a promising therapeutic approach to regenerate damaged structures of the respiratory system and restore lung function. The aim of this study was to provide a quantitative synthesis of the efficacy profile of stem cell-based regenerative therapies and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 93 publications
0
21
0
Order By: Relevance
“…COPD is a common and preventable respiratory disease characterized by persistent airfow limitation. Except β2 agonist and glucocorticoid, growing novel strategies, such as Nrf2 agonist, prebiotics, stem cell transplantation, and oligonucleotides have been considered [34][35][36][37][38][39][40], but there is no efcient treatment to prevent its progression. Patients are treated with drugs to keep the airway unobstructed and improve the symptoms of dyspnea, chest tightness, and wheezing [13].…”
Section: Discussionmentioning
confidence: 99%
“…COPD is a common and preventable respiratory disease characterized by persistent airfow limitation. Except β2 agonist and glucocorticoid, growing novel strategies, such as Nrf2 agonist, prebiotics, stem cell transplantation, and oligonucleotides have been considered [34][35][36][37][38][39][40], but there is no efcient treatment to prevent its progression. Patients are treated with drugs to keep the airway unobstructed and improve the symptoms of dyspnea, chest tightness, and wheezing [13].…”
Section: Discussionmentioning
confidence: 99%
“…216 Progressive destruction of alveolar tissue is one of the hallmarks of COPD, so there is increasing research on regenerative therapy based on stem cells and their derived products for repairing alveolar structure and restoring function. 217 A study of a rat COPD model induced by cigarette exposure has shown that human umbilical cord mesenchymal stem cell (hUC-MSC)-derived extracellular vesicles (EVs) are effective in ameliorating COPD-induced inflammation.…”
Section: Clinical and Potential Therapeutic Interventions In Copdmentioning
confidence: 99%
“…The results of a 52‐week randomized clinical trial have shown that triple therapy with twice‐daily inhaled glucocorticoid (160 or 320 μg of budesonide), long‐acting muscarinic antagonist (18 μg of glycopyrrolate), and long‐acting β2‐agonist (9.6 μg of formoterol) causes a lower rate of moderate‐to‐very‐severe COPD exacerbations than glycopyrrolate–formoterol or budesonide–formoterol 216 . Progressive destruction of alveolar tissue is one of the hallmarks of COPD, so there is increasing research on regenerative therapy based on stem cells and their derived products for repairing alveolar structure and restoring function 217 . A study of a rat COPD model induced by cigarette exposure has shown that human umbilical cord mesenchymal stem cell (hUC‐MSC)‐derived extracellular vesicles (EVs) are effective in ameliorating COPD‐induced inflammation.…”
Section: Therapeutic Potential Of Lung Regeneration In Lung Diseasementioning
confidence: 99%
“…As shown in figure 2, we attempted to synthesise the therapeutic potential resulting from different factors secreted by mesenchymal stromal/stem cells (MSCs) (secretome), as well as the physiological processes of these different factors that can act directly or indirectly as potential targets for cell-based therapy for COPD and other chronic diseases, through a paracrine mechanism or distant from the originating cell (MSC extracellular vesicles) or by cell-to-cell contact. This understanding of COPD in a broader context of pathogenesis and pathophysiology opens up new avenues of opportunity for early diagnosis, effective forms of prevention, the possibility of early intervention and new therapeutic approaches [22][23][24][25][26][27][28][29][30][31][32][33]. In this context, cell-based therapies have arisen as potentially promising new therapeutic approaches and different cell-based therapies have been proposed and tested in pre-clinical models of COPD/emphysema.…”
Section: Introductionmentioning
confidence: 99%